Resureksi perspektif holistik melalui pembelajaran ilmu pengetahuan sosial - Daya Negri Wijaya (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
The teaching of social studies is often realized by the student as a confusing subject. This is common considering the students’ holistic point of view. The holistic view could open the comprehensive perspective or the impartial perspective. If the teaching is run by partial perspective but the students’ way of thinking seems to be holistic; therefore it will be happened a confusing teachers and students in the context of teaching and learning process. This article wants to re-vitalize the holistic view in social studies teaching. Therefore, this article will focus on the implementation of holistic perspective in planning, acting, and evaluating social studies teaching.Keywords: social studies teaching, holistic, resurrection, social scientist http://dx.doi.org/10.17977/um022v1i22016p107